2023
DOI: 10.1111/1753-0407.13376
|View full text |Cite
|
Sign up to set email alerts
|

Longer leukocyte telomere length increases cardiovascular mortality in type 2 diabetes patients

Abstract: Aims Leukocyte telomere length (LTL), as a biomarker of biological aging, is associated with the prevalence and complications of diabetes. This study aims to investigate the associations between LTL and all‐cause and cause‐specific mortality in patients with type 2 diabetes. Methods All participants with baseline LTL records were included from the National Health and Nutrition Examination Survey 1999–2002. Death status and its causes were ascertained for National Death Index based on International Classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…A recently published study investigated the association between telomere length and mortality among patients with diabetes and found that TL was not significantly associated with death from any cause. The authors even found that longer TL was associated with an increased risk of CVD mortality, contradicting previous studies [ 12 ]. In our study, we examined the association between LTL and CVD mortality among middle-aged and older participants without prior CVD.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…A recently published study investigated the association between telomere length and mortality among patients with diabetes and found that TL was not significantly associated with death from any cause. The authors even found that longer TL was associated with an increased risk of CVD mortality, contradicting previous studies [ 12 ]. In our study, we examined the association between LTL and CVD mortality among middle-aged and older participants without prior CVD.…”
Section: Discussioncontrasting
confidence: 57%
“…However, some studies have contradicted these findings by suggesting that LTL is not a significant risk factor for the development of cardiovascular disease (CVD) [ 10 , 11 ]. More recently, Chen et al discovered a positive association between longer LTL and increased risk of CVD mortality among patients with type-2 diabetes in the United States (US) [ 12 ]. Consequently, the role of TL in the development of age-related diseases and long-term prognosis remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Shorter LTL is associated with an increased risk of mortality in contemporary humans, particularly for non-cancer causes of death such as cardiovascular disease, and LTL may serve as a marker for the natural lifespan limit in humans [ 10 ]. However, studies have found contradictory results, indicating that longer leukocyte telomere length increases the risk of cardiovascular mortality in patients with type 2 diabetes [ 11 ]. Shorter TL is strongly correlated with multiple components of metabolic syndrome, such as abdominal obesity, dyslipidemia, hyperglycemia, and overall metabolic health, and it also serves as a predictor for an unfavorable metabolic profile [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%